Recovery from Cogwheel Rigidity and Akinesia and Improvement in Vibration Sense and Olfactory Perception following Removal of an Epoxy-Oleic Acid DNA Adduct - Monro, Jean A. (Case Rep Med, 2017)
The epoxy fatty acid cis-12,13-epoxy-oleic acid, which acts as a DNA adduct, may be generated during long-term storage of many seed oils, including those used in cooking, with frying oils and fried foods being a major source in the modern human diet. Removal of this epoxy fatty acid from the locus of the N-formyl peptide receptors was associated with recovery from cogwheel rigidity and akinesia as well as with improvement in vibration sense and olfactory perception.